A transient early HBV‐DNA increase during PEG‐IFNα therapy of hepatitis D indicates loss of infected cells and is associated with HDV‐RNA and HBsAg reduction. Issue 2 (12th December 2020) - Anastasiou, Olympia E.; Yurdaydin, Cihan; Maasoumy, Benjamin; Hardtke, Svenja; Caruntu, Florin Alexandru; Curescu, Manuela G.; Yalcin, Kendal; Akarca, Ulus S.; Gürel, Selim; Zeuzem, Stefan; Erhardt, Andreas; Lüth, Stefan; et al.
Abstract: HBV‐DNA levels are low or even undetectable in the majority HDV‐infected patients. The impact of PEG‐IFNα on HBV‐DNA kinetics in HDV‐infected patients has not been studied in detail. We analysed data of a prospective treatment trial where 120 HDV‐RNA–positive patients were randomized to receive PEG‐IFNα‐2a plus tenofovir‐disoproxil‐fumarate (PEG‐IFNα/TDF, n = 59) or placebo (PEG‐IFNα/PBO; n = 61) for 96 weeks. At week 96, HBV‐DNA was still quantifiable in 71% of PEG‐IFNα/PBO‐treated patients but also in 76% of PEG‐IFNα/TDF‐treated patients, despite low HBV‐DNA baseline values. Surprisingly, a transient HBV‐DNA increase between weeks 12 and 36 was observed in 12 in PEG‐IFNα/TDF‐treated and 12 PEG‐IFNα/PBO‐treated patients. This increase was positively associated with HBsAg loss [( P  = 0.049, odds ratio (OR) 5.1] and HDV‐RNA suppression ( P  = 0.007, OR 4.1) at week 96. Biochemical markers of cell death (M30 and ALT) were higher during the HBV‐DNA peak but no distinct systemic immune pattern could be observed by screening 91 soluble inflammatory markers. In conclusion, an early increase in HBV‐DNA during PEG‐IFNα‐2a therapy occurred in more than 20% of patients, even in TDF‐treated patients. This transient HBV‐DNA rise may indicate PEG‐IFNα–induced cell death and lead to long‐term HDV‐RNA suppression and HBsAg loss.